Контроль освоения компетенций эндодонтического лечения выпускниками МГМСУ (Эндодонтия Today, 2020)
As part of the final state certification of graduates with a degree in Dentistry, which was implemented in 3 stages: the final computer testing, assessment of practical skills and an interview focused on monitoring the development of competencies of endodontic treatment. Graduates demonstrate the stages of endodontic treatment in dental simulators: Disclosure cavity with subsequent biomechanical cleaning and shaping and obturation of the root canal, using modern techniques and materials.